2023
DOI: 10.1038/s41419-023-05637-y
|View full text |Cite
|
Sign up to set email alerts
|

TRAF4-mediated ubiquitination-dependent activation of JNK/Bcl-xL drives radioresistance

Abstract: The E3 ligase TNF receptor-associated factor 4 (TRAF4) is upregulated and closely associated with tumorigenesis and the progression of multiple human malignancies. However, its effect on radiosensitivity in colorectal cancer (CRC) has not been elucidated. The present study found that TRAF4 was significantly increased in CRC clinical tumor samples. Depletion of TRAF4 impaired the malignant phenotype of CRC cells and sensitized irradiation-induced cell death. Irradiation activated the c-Jun N-terminal kinases (J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Recently study showed that TRAF4-mediated atypical ubiquitination of SET domain bifurcated 1 induced the activation of the AKT pathway to facilitate glioblastoma proliferation 50 . TRAF4 facilitates the ubiquitination of JNK1/2 and activates the JNK/c-Jun pathway to drive radioresistance in colorectal cancer 10 . Moreover, TRAF4 catalyzes CHK1 ubiquitination and promotes DNA damage response to confer chemoresistance 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently study showed that TRAF4-mediated atypical ubiquitination of SET domain bifurcated 1 induced the activation of the AKT pathway to facilitate glioblastoma proliferation 50 . TRAF4 facilitates the ubiquitination of JNK1/2 and activates the JNK/c-Jun pathway to drive radioresistance in colorectal cancer 10 . Moreover, TRAF4 catalyzes CHK1 ubiquitination and promotes DNA damage response to confer chemoresistance 16 .…”
Section: Discussionmentioning
confidence: 99%
“…E3 ubiquitin ligases are crucial in cancer progression as they catalyze ubiquitination by transferring ubiquitin to cancer-associated proteins 7 , 8 . Tumor necrosis factor receptor-associated factor 4 (TRAF4), a typical ring domain E3 ubiquitin ligase 9 , is frequently overexpressed and is correlated with poor prognosis in human malignancies, including colorectal 10 , prostate 11 , lung 12 cancer, and glioblastoma 13 . TRAF4 functions as an oncoprotein to regulate metastasis 14 , oncogenesis 15 , and therapeutics resistance 10 , 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the colony formation ability of CAL27 and SCC9 cells, anchorage-independent cell growth assay and plate colony formation assay were performed as described previously 23 . Briefly, for anchorage-independent cell growth assay, OSCC cells were resuspended at a concentration of 8×10 3 cells/ml and inoculated in 6-well plates containing Basal Medium Eagle (0.6% agar, 10% FBS, and different concentrations of butein.…”
Section: Methodsmentioning
confidence: 99%
“…BCA assay (#23228, Pierce, Rockford, IL) was used for protein concentration following the standard procedures. Western blotting was performed as previously described 31 , 32 . Briefly, WCE was boiled with loading buffer at 95°C for 5 min and subjected to SDS-PAGE followed by electrotransfer to the PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%